Illuminating photoreceptors: TGFβ signaling modulates the severeness of retinal degeneration - Aaron Schroers; Andreas Neueder; Isabel Massoudy; Andrea E. Dillinger; Süleyman Ergün; Barbara M. Braunger; Anja Schlecht (Cell Death Discovery)
Abstract In various ocular diseases, retinal degeneration (RD) is a clinical symptom that can lead to irreversible vision loss. These diseases include age-related macular degeneration (AMD) and retinitis pigmentosa (RP). Retinal degeneration describes a process during which the retina deteriorates due to the gradual death of photoreceptor cells. Although extensive research has been pursued to identify the underlying pathomechanisms, the precise molecular mechanisms that leads to photoreceptor death remains unclear. In this study, we combined the mouse model of light-induced photoreceptor degeneration with single-cell RNA sequencing to decipher the transcriptional response of degenerating photoreceptor cells. We additionally performed pseudotime analysis of gene expression changes for both the control and light-damaged photoreceptor clusters to analyze the extent of degeneration following a virtual trajectory of severeness. We found a transcriptional heterogeneity of rod photoreceptors in both control and degenerative conditions, and mapped several rod clusters which strongly differ in their transcriptional profile. We defined one of these clusters as the predominant disease-associated rod cluster, containing the most severely damaged rod cells. Pseudotime analysis demonstrated a strong regulation of TGFβ signaling and the RNA-induced silencing complex (RISC) in light-damaged photoreceptors suggesting a pivotal role of these mediators in retinal degeneration.